Conceptual Explanation of Spatial Mismatch Fields of Job and Residence in urban spaces with emphasis on Iran - tajoddin Karami; mohamad soleimani; taher parizadi; somayeh teimory (جغرافیا و توسعه, 2021)
Spatial Mismatch theory is one of the theories that examine poverty and inequality in the social-Spatial structure of cities. The aim of the present study was to "conceptually explain the grounds for Spatial Mismatch of work and residence", especially in the cities of developing countries and Iran. This research is theoretical-applied in nature and descriptive-analytical in terms of method. In addition, discourse analysis has been used to explain the fields of formation and the lack of Spatial Mismatch. According to the findings of the present study, Spatial Mismatches in the Great Fields (global and Inclusive changes such as the expansion of Ford-Keynesian and neoliberal , Post Fordism) and its most objective layer (the inequality between access to Appropriate work and access to housing in urban structure and space), are similar.However, geographically, the focus of Spatial Mismatch in developing countries, in contrast to the US, is mostly on the suburb of cities.While Spatial Mismatch in the United States is influenced by unequal racial-ethnic contexts, development of transportation technology, suburbanization, industrialization, and the establishment of industries and factories, in developing countries it is mainly due to its "unequal structure of international economic relations," "implementation." External development strategies include "unequal socio-spatial construction", "getting caught up in the traps of development traps" (political instability, selling natural resources, spreading the consequences of neighborly instability, inefficient governance), and “traps of poverty and corruption" and “unstable pattern of urban development".